Sistem Keamanan Data Privacy Pada Jaringan Sensor Nirkabel Menggunakan Teknik Routing: Sistem Keamanan Data Privacy - Yanti, Yeni; Hidayat, Taufik (Universitas PGRI Kanjuruhan Malang, 2024)
Wireless Sensor Networks (WSN) have attracted the attention of researchers in recent years. WSN , is increasingly using it in various fields. Even though the use of WSNs is becoming more widespread, they are often vulnerable to security attacks. Therefore, it is important to have a strong security system that can provide users with a sense of security and comfort in sending data via WSN. Sending data via WSN also carries significant security risks, especially when the data sent is related to the sender's location. Therefore, this research aims to analyze the scalability of the security system in sending data via WSN using the LSP routing technique. The main focus of this research is protecting data source location information in the context of WSN using LSP Routing techniques. In the tests carried out in this research, a sinkhole attack was used which aims to detect nodes. The research results show that the data transmission rate from the node to the CH increases by 50%, 75%, and 90% in each cycle when the security system is implemented. However, only around 25% and 50% of node attacks in the data transmission process are successfully detected by the sinkhole. The impact of such attacks is felt on the nodes operating in the network, with approximately 95% of nodes eventually going down at the end of the cycle when no security systems are in place. However, when a security system is implemented, only about 60% of nodes fail to send data to their destination.